Governance and Institutional Innovation: The need for strategic management - Perpetua McDonagh; Patrick Commins; Anthony Leavy (European Regional Science Association (ERSA), 1998)
Within a comparatively short time there has emerged in Ireland an ad hoc ensemble of initiatives, funds and organisations pursuing aspects of rural development. As a result development policy is faced with a series of institutional and organisational questions (NESC, 1994: 115). These questions concern central-local relationships, possible overlap between agencies, the appropriate spatial units for different programmes, the choice between territorially-based organisations versus sectoral agencies, and accountability in regard to the use of public funds. This paper presents some results from a prospective model designed to facilitate analysis of the policy and institutional environment pertaining to rural development in Ireland. It identifies weaknesses in the institutional fabric: the high degree of centralisation of power and responsibility within agencies; related to this, the sharp compartmentalisation among agencies which act independently of each other, in singularly focusing on separately defined areas of administration; the proliferation of agencies and programmes, this partly reflects the influence of EU funded programmes which have promoted ?bottom up? approaches; the lack of an adequate sub-national spatial focus in policy implementation, and a ?democratic deficit? to the extent that emerging new partnerships are not inclusive of local representative democratic structures. Policy instruments are evaluated and issues for future policy emphasis explored. The paper concludes that organisational structures are vitally important to successful policy intervention in lagging regions. Within the Irish system institutional change is urgently needed.
Keywords: 330